Salinity tolerance mechanisms and their breeding implications - Mandeep Singh (SpringerOpen, 2021)
Abstract Background The era of first green revolution brought about by the application of chemical fertilizers surely led to the explosion of food grains, but left behind the notable problem of salinity. Continuous application of these fertilizers coupled with fertilizer-responsive crops make the country self-reliant, but continuous deposition of these led to altered the water potential and thus negatively affecting the proper plant functioning from germination to seed setting. Main body Increased concentration of anion and cations and their accumulation and distribution cause cellular toxicity and ionic imbalance. Plants respond to salinity stress by any one of two mechanisms, viz., escape or tolerate, by either limiting their entry via root system or controlling their distribution and storage. However, the understanding of tolerance mechanism at the physiological, biochemical, and molecular levels will provide an insight for the identification of related genes and their introgression to make the crop more resilient against salinity stress. Short conclusion Novel emerging approaches of plant breeding and biotechnologies such as genome-wide association studies, mutational breeding, marker-assisted breeding, double haploid production, hyperspectral imaging, and CRISPR/Cas serve as engineering tools for dissecting the in-depth physiological mechanisms. These techniques have well-established implications to understand plants’ adaptions to develop more tolerant varieties and lower the energy expenditure in response to stress and, constitutively fulfill the void that would have led to growth resistance and yield penalty.